2018
DOI: 10.1037/xlm0000520
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic effects in second-language spoken-word recognition.

Abstract: Evidence from both alphabetic and nonalphabetic languages has suggested the role of orthography in the processing of spoken words in individuals' native language (L1). Less evidence has existed for such effects in nonnative (L2) spoken-word processing. Whereas in L1 orthographic representations are learned only after phonological representations have long been established, in L2 the sound and spelling of words are often learned in conjunction; this might predict stronger orthographic effects in L2 than in L1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Instead, the fact that L2-specific form priming effects persist even in overt visual priming, where L1 speakers normally show at least a trend for inhibition, suggests that, as claimed by Heyer and Clahsen [20], the larger reliance on (orthographic) surface form properties of complex words in L2 speakers is a general property of L2 visual word recognition, at least in lexical decision tasks. This is in line with previous L2 research from other domains [2125].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Instead, the fact that L2-specific form priming effects persist even in overt visual priming, where L1 speakers normally show at least a trend for inhibition, suggests that, as claimed by Heyer and Clahsen [20], the larger reliance on (orthographic) surface form properties of complex words in L2 speakers is a general property of L2 visual word recognition, at least in lexical decision tasks. This is in line with previous L2 research from other domains [2125].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, the results from several studies investigating visual [21, 22] as well as auditory lexical processing [2325] suggest that L2 speakers focus relatively more on surface form properties of words than L1 speakers, which, in priming studies, may lead to increased form priming effects. There is at least some evidence suggesting that such L2-specific form priming effects may even emerge when primes and targets are presented in different modalities.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting component of the current study is the direct comparison of native versus non-native language. As briefly summarized in the Introduction, in previous work we (Qu, Cui & Damian, 2017) compared effects of orthography in spoken Chinese word perception between Chinese monolinguals and Tibetan-Chinese bilinguals, and found that orthography affected perception more so for bilingual L2 listeners than monolinguals, as evidenced by a significant group x orthography interaction in a joint analysis. By contrast, in the present study the orthographic effect in spoken production was numerically somewhat larger Orthography in L2 Spoken Word Production 15 what we previously found for monolinguals (Qu & Damian, 2019) but the joint analysis did not show a significant interaction.…”
Section: Discussionmentioning
confidence: 99%
“…In language comprehension, very few studies have explored this issue, but the limited evidence suggests that non-native listeners engage orthographic access to the same, or even a greater, extent than native listeners. For instance, Qu, Cui, and Damian (2017) presented Tibetan non-native Chinese speakers with two successive spoken Chinese words on a given trial, and participants were asked to judge whether or not the two words were semantically related. Pairs were either semantically related, orthographically related, or unrelated.…”
Section: Orthographic Effects In Second-language Processingmentioning
confidence: 99%
“…Therefore, orthographic representations help learners to specify and clarify phonological forms, leading to distinctive and robust phonological representations. Recent evidence suggests that the orthographic facilitation effect is still more pronounced in L2 when compared to L1 learners (Qu et al 2018). A possible explanation is that, in L2 learners, language representations are often acquired through spoken and written language input in parallel.…”
Section: Inspection Ofmentioning
confidence: 99%